2014
DOI: 10.1515/chem-2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

Electron heating modes and frequency coupling effects in dual-frequency capacitive CF4 plasmas

Abstract: Two types of capacitive dual-frequency discharges, used in plasma processing applications to achieve the separate control of the ion flux, Г i , and the mean ion energy, , at the electrodes, operated in CF 4 , are investigated by particle-in-cell simulations: (i) In classical dual-frequency discharges, driven by significantly different frequencies (1.937 MHz + 27.12 MHz), and Г i are controlled by the voltage amplitudes of the low-frequency and high-frequeny components, Φ LF and Φ HF , respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 77 publications
(113 reference statements)
0
37
0
Order By: Relevance
“…Transitions between the DA-mode and the α-mode have been demonstrated by both simulations and experiments on CF 4 discharges [13,70] where by increasing the operating pressure at a fixed applied voltage, a transition from the α-mode to the DA-mode is induced. Note that the CF 4 discharge is weakly electronegative at 75 mTorr while it is strongly electronegative at 600 mTorr [14]. Also by increasing the voltage at a fixed pressure, a transition from the DA-mode to the α-mode is observed in a CF 4 discharge [13].…”
Section: Resultsmentioning
confidence: 99%
“…Transitions between the DA-mode and the α-mode have been demonstrated by both simulations and experiments on CF 4 discharges [13,70] where by increasing the operating pressure at a fixed applied voltage, a transition from the α-mode to the DA-mode is induced. Note that the CF 4 discharge is weakly electronegative at 75 mTorr while it is strongly electronegative at 600 mTorr [14]. Also by increasing the voltage at a fixed pressure, a transition from the DA-mode to the α-mode is observed in a CF 4 discharge [13].…”
Section: Resultsmentioning
confidence: 99%
“…This is a consequence of the widening of the sheath due to the higher voltage, which, on the other hand, does not contribute significantly to higher ionisation because of its low frequency, i.e. the frequency coupling mechanism [25,26]. At the highest value of the SEEC, γ = 0.4, the enhanced sheath voltage contributes to the ionisation as it accelerates secondary electrons to high energies, which can then ionise as well.…”
Section: Classical Dual-frequency Excitationmentioning
confidence: 99%
“…Properties of plasma sources, operated in various gases and under different conditions, driven by DF waveforms have thoroughly been studied [21][22][23][24]. These investigations have also revealed that the independent control of ion flux and energy is limited by "frequency coupling" effects [25,26] and secondary electron emission from the electrodes [27,28]. A further major step in the control of ion properties has been the discovery of the Electrical Asymmetry Effect (EAE) [29,30] in 2008, by using a base frequency and its second harmonic to excite the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The ion flux is comparatively insensitive to the change in the phase shift meaning that the two quantities can be controlled independently of one another. Since the original study many investigations have demonstrated this effect through both simulation and experiment and extended it to the use of more than two frequencies to increase the amplitude asymmetry of the waveform [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. It has also been demonstrated that an electrical asymmetry can be generated using sawtooth-like waveforms where the rise and fall times of the voltage waveform differ [41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 97%
“…For example, it has been shown that the dc self-bias formed in electrically asymmetric plasmas can change over a wide range dependent on the gas in which the plasma is formed [44] and can thus be difficult to predict. The electronegativity of the plasma, which in part determines the electron heating mode [52], has been found to be particularly important in this regard [31,37,44,48].…”
Section: Introductionmentioning
confidence: 99%